A review of smartphones‐based indoor positioning: Challenges and applications. Issue 1 (30th March 2021) - Nguyen, Khuong An; Luo, Zhiyuan; Li, Guang; Watkins, Chris
Abstract: The continual proliferation of mobile devices has encouraged much effort in using the smartphones for indoor positioning. This article is dedicated to review the most recent and interesting smartphones‐based indoor navigation systems, ranging from electromagnetic to inertia to visible light ones, with an emphasis on their unique challenges and potential real‐world applications. A taxonomy of smartphone sensors will be introduced, which serves as the basis to categorise different positioning systems for reviewing. A set of criteria to be used for the evaluation purpose will be devised. For each sensor category, the most recent, interesting, and practical systems will be examined, with detailed discussion on the open research questions for the academics, and the practicality for the potential clients.